1999
DOI: 10.1002/(sici)1096-8652(199912)62:4<228::aid-ajh5>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral and meningeal multiple myeloma after autologous stem cell transplantation. A case report and review of the literature

Abstract: Meningeal involvement of multiple myeloma is a very rare complication. Defining men-ingeal myelomatosis (MeM) as the presence of plasma cells in the cerebrospinal fluid in a patient with multiple myeloma, we have found 53 previously reported cases in the literature, where the diagnosis MeM has been made while the patient was alive. Using Kaplan Meier statistics we have found the median survival, from the time of diagnosis of MeM, to be 1.5 months. We report a case with MeM and possible cerebral myeloma shortly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
95
1
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(108 citation statements)
references
References 37 publications
6
95
1
6
Order By: Relevance
“…We found only eight cases of CNS-MM diagnosed by means of flow cytometry. 8,15,16,18,20,[22][23][24] Thus, in the current paper we report both our experience and a review of previous cases investigated by flow cytometric methods.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found only eight cases of CNS-MM diagnosed by means of flow cytometry. 8,15,16,18,20,[22][23][24] Thus, in the current paper we report both our experience and a review of previous cases investigated by flow cytometric methods.…”
Section: Introductionsupporting
confidence: 89%
“…We found that a total number of 187 cases had been reported until 2012. [3][4][5][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The same case was described in two different instances. 19,23 Therefore, we reviewed review articles and single case reports in order to obtain more information about patients characteristics, the method used to detect plasma cells in the CSF and plasma cell phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Often, transient neurological improvement is seen, but progression and death inevitably follow shortly after.…”
mentioning
confidence: 99%
“…Treatment options include intrathecal chemotherapy, systemic chemotherapy, cranial irradiation or a combination. The prognosis of CNS multiple myeloma is poor, with an overall median survival from the time of diagnosis to death of 2.0 months (range 0.1-25 months) [2].…”
Section: Discussionmentioning
confidence: 99%